Prevalence of Pseudomonas aeruginosa Isolates in Drinking Water from Health Region 9 - Watcharawichanan, Pongpan; Inthiyot, Patcharee; Kaewsena, Kanokwan; Kapphimai, Watcharapol (Journal of the office of disease prevention and control 9 Nakhon Ratchasima, 2024)
The study aimed to investigate the prevalence and evaluate the microbiological quality of drinking water through the analysis of Coliform bacteria, Escherichia coli, Salmonella spp., Staphylococcus aureus, and Pseudomonas aeruginosa in samples sourced from producers of bottled and containerized drinking water. A total of 241 samples were collected in Health Region 9 between January and May 2022. Microbiological analyses were performed using standard procedures specified by the American Public Health Association (APHA) and the International Organization for Standardization (ISO) at the Regional Medical Sciences Center 9, Nakhon Ratchasima. The results of the microbiological quality revealed that the water did not pass the standard criteria level, as Coliform bacteria were detected at 13.28%, and E. coli was present at 1.66%. These findings indicated microbial contamination and inadequate production standards. P. aeruginosa was detected at 19.50%, showing a significant statistical association with Coliforms bacteria contamination (p <0.0001). Sensitivity testing of 28 P. aeruginosa isolates using Disc Agar Diffusion for 12 antibiotics showed that 22 isolates were sensitive to amikacin, gentamicin, tobramycin, cefepime, ceftazidime, ciprofloxacin, levofloxacin, piperacillin, piperacillin/tazobactam, imipenem, meropenem, and colistin. Three isolates exhibited intermediate resistance to ceftazidime and cefepime, with two isolates being resistant to cefepime only, and one isolate resistant to ceftazidime only. MIC testing was conducted on isolates that exhibited either susceptibility or intermediate resistance to antibiotics. The results revealed that all five isolates were susceptible to amikacin, gentamicin, cefepime, ciprofloxacin, piperacillin/tazobactam, meropenem, and colistin. Additionally, the isolates showed resistance to imipenem. Moreover, MIC and MBC testing against extracts of Syzygium aromaticum showed values of 2.56 mg/mL, while Stephania suberosa demonstrated respective values of 5.12 mg/mL and 10.24 mg/mL. This study provides insights into antibiotic resistance in drinking water, contributing to the monitoring and control of contamination risks. Furthermore, the utilization of plant extracts, particularly from cloves (S. aromaticum), demonstrated significant inhibitory effects on P. aeruginosa, suggesting their potential use in combination with antibiotics to reduce antibiotic consumption in the future.